Analisis Korelasi Lama Duduk dan Usia dengan Fleksibilitas Lumbal Menggunakan Modified Schober Test pada Karyawan PT Bank Syariah Indonesia Lhokseumawe - Nur Sakinah Nasution; Nora Maulina (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Lumbar flexibility refers to the maximum capacity of the muscles in the lumbar spine to move freely. Impairment in functional movement may lead to restricted mobility, which can be influenced by disruption of biomotor components, particularly lumbar spinal flexibility. Flexibility may be affected by both internal and external factors, including age and duration of sitting during work. This study aimed to analyze the relationship between sitting duration and age with lumbar flexibility using the Modified Schober Test among employees of PT Bank Syariah Indonesia, Lhokseumawe City. This study applied a cross-sectional design and was conducted in December 2023 in the prayer room area of the PT Bank Syariah Indonesia branch office. Sampling was carried out using a total sampling technique involving 46 respondents. Data collection was performed by measuring lumbar flexibility using the Modified Schober Test method. The results showed that the highest proportion of respondents had limited lumbar flexibility, accounting for 24 respondents (52.2%). The majority of respondents had a sitting duration of 7–9 hours, totaling 26 respondents (56.5%), while the largest age group was 26–35 years, consisting of 23 respondents (50%). Spearman-Rank correlation analysis demonstrated a relationship between sitting duration and lumbar flexibility measured by the Modified Schober Test (r = 0.662). In addition, the relationship between age and lumbar flexibility also showed a correlation based on the Spearman-Rank test (r = -0.321). The study concluded that longer sitting duration and increasing age were associated with greater limitation in lumbar flexibility among employees of PT Bank Syariah Indonesia, Lhokseumawe City.